问题 解答题
脱式计算,注意使计算简便
1
6
+
3
4
×
2
3
÷2
3
4
+
1
2
-
7
12
)×24
17
24
×
3
4
+
17
24
÷4
2-
6
13
÷
9
26
-
2
3

[4-(
3
4
-
3
8
)]×
4
29
答案

(1)

1
6
+
3
4
×
2
3
÷2

=

1
6
+
3
4
×
2
3
×
1
2

=

1
6
+
1
4

=

5
12

(2)(

3
4
+
1
2
-
7
12
)×24

=

3
4
×24+
1
2
×24-
7
12
×24,

=18+12-14,

=30-14,

=16;

(3)

17
24
×
3
4
+
17
24
÷4

=

17
24
×
3
4
+
17
24
×
1
4

=

17
24
×(
3
4
+
1
4
),

=

17
24
×1,

=

17
24

(4)2-

6
13
÷
9
26
-
2
3

=2-

6
13
×
26
9
-
2
3

=2-

4
3
-
2
3

=2-(

4
3
+
2
3
),

=2-2,

=0;

(5)[4-(

3
4
-
3
8
)]×
4
29

=[4-

3
8
4
29

=3

5
8
×
4
29

=

1
2

填空题
单项选择题